(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The research studies because construction site accidents are caused in India and how they can reduce constructional accidents. This Article analyzes in greater detail the factors that affect safety at construction sites. Discuss the strategies that companies in India follow to provide protection at work and, ultimately, look at the best approaches to introduce safety management procedures in the construction industry.